1983
DOI: 10.5271/sjweh.2412
|View full text |Cite
|
Sign up to set email alerts
|

Increased uptake of serotonin in platelets from car painters occupationally exposed to mixtures of solvents and organic isocyanates.

Abstract: BEVING H, MALMGREN R, OLSSON P, TORNLING G, UNGE G. Increased uptake of serotonin in platelets from car painters occupationally exposed to mixtures of solvents and organic isocyanates. Scand j work environ health 9 (1983) 253-258. Twelve car painters occupationally exposed to mixtures of solvents and organic isocyanates were investigated concerning serotonin uptake in platelets. The data from the exposed workers were compared to data from a reference group consisting of 50 nonexposed volunteers. The mean plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This is an important parameter in uptake studies, because induced effects hereon might explain the observed effects on uptake. This study indicate that the solvent induced effect on platelet 5-HT uptake, reported by Beving et al (1983), is not due to solvent induced reduction of 5-HT concentration at time zero of incubation. It also indicates a solvent induced effect on the 5-HT uptake mechanism.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…This is an important parameter in uptake studies, because induced effects hereon might explain the observed effects on uptake. This study indicate that the solvent induced effect on platelet 5-HT uptake, reported by Beving et al (1983), is not due to solvent induced reduction of 5-HT concentration at time zero of incubation. It also indicates a solvent induced effect on the 5-HT uptake mechanism.…”
Section: Resultssupporting
confidence: 58%
“…Recently Beving et al (1983) showed significantly accelerated platelet 5-HT uptake rate of platelets isolated from humans (n = 12) exposed to organic solvents compared to a nonexposed control group (n = 50). Similar effects on both platelet and synaptosomal 5-HT uptake are shown to be induced by a number of neurotoxic agents (Komulainen & Tuomisto 1981a, b & c;Tuomisto & Komulainen 1983a & b).…”
Section: Resultsmentioning
confidence: 99%
“…The intrapersonal variations in the content of platelet serotonin over time, at least for several months, are small ( Hervig et al ., 1996 ). Also, endogenous serotonin influences platelet functions, assayed as uptake or release of serotonin in vitro ( Beving et al ., 1983 ; Hervig & Farstad, 1996) and viability in vivo ( Aranda et al ., 1996 ).…”
mentioning
confidence: 99%